Role of user interfaces in access to digital content - Vrana, Radovan (2006)
User interfaces are principal access points to resources of digital content on the Internet. They are especially important for libraries offering services on the Internet, including digital libraries. As the most prominent part of the libraries and library Web sites present on the Internet, the user interfaces are exposed to existing and potential library users and their constant analysis and evaluation. By giving focus on user interfaces we implicitly mean to graphical user interfaces (GUI), the richest and the most common form of user interfaces. GUIs exist for approximately four decades, and during that period, they have gone under many transformations. One of the latest transformations came with the World Wide Web and introduction of a new type of applications – Web applications. Web applications introduced new concepts of the user interface design. During the 1990s along came digital libraries, with sometimes very different and complex user interfaces in comparison to the mainstream Web interfaces. It is worth noting that a significant number of the existing user interfaces in digital libraries came to existence as an experiment and as a part of the early development projects of digital libraries, sometimes tracing new routes for the development of user interface that came afterwards. The focus of user interface development should be on users. However, large number of Web user interfaces was developed without any research on target user community. Consequently, some existing user interfaces are modeled upon presumptions about potential users rather than on actual user needs and expectations. In support to this view, Ioannidis selected some thoughts from DELOS meetings regarding users and future of digital libraries and the role of users: “ Future digital libraries must offer content and services that are adapted (in terms of substance and presentation) to the personal needs of the user. These are implied by the user’ s preferences, task, information needs, background, history, device, location, time of request and other characteristics that essentially define the user’ s context.“ (Ioannidis, 2005, p. 258). User interfaces can also serve as a means for evaluation of digital libraries or their respective parts. Presently, this is a difficult task since the evaluation criteria for digital libraries are still being developed. In contrast, there are many very diverse criteria for evaluation of general purpose Web sites available on the Internet, focusing mostly on content of the analyzed Web site, information authenticity and accuracy, and less on the user interface. The user interface, of course, is just a vehicle for accessing the content, and it shouldn’ t become an obstacle for the user when accessing particular digital content. Since the advent of the World Wide Web, Web sites (the main operational environment for digital libraries) have become more technically advanced. Today, they run significant number of back-end applications having a complex front-end - user interfaces. As complexity of back-end and front-end parts of the Web sites grew, so did a necessity for understanding of needs and wishes of actual users which would help their development. When speaking about development of Web sites in general and sources of digital content such as digital libraries in particular, we should consider the term of usability. Usability is a quality attribute that assesses how easy user interfaces are to use and it also refers to methods for improving ease-of-use during the design process (Nielsen, 2003). There is more than one method for testing Web site usability (including user interfaces). One can collect data while observing users who actually use particular Web site (with consent given by the users) and conversing with them, or asking users to think aloud while completing given task, and at the same time videotaping them for later analysis. Other methods may include: comparative study of selected (Web site) interfaces, and is usually done against some criteria list, use of benchmarks (measuring time for task completion etc.), asking the user questions that are related to the task which should be completed, user studies (surveys, interviews, focus groups) etc. The development of user interfaces is also covered by ISO standards (ISO/CD 9241-151 Ergonomics of human-system interaction - Software ergonomics for World Wide Web user interfaces and ISO 9241-9 do ISO 9241-17), guidelines, and examples of best practice. Some of these documents can offer a good starting point for evaluation of user interfaces, and some can provide valuable framework for development of criteria for development and evaluation of user interfaces. In brief, this poster will present a selection of digital libraries interfaces which can serve as a starting point for commentaries on their compliance with selected criteria selected from available literature on digital library development and from Web sites dedicated to usability and Web information resources design and evaluation.
Projekt MZOS
ENG